Optimization of aluminumand its alloys doping by ionic-beamplasmacoating; IOP Conference Series: Materials Science and Engineering; Vol. 124 : Mechanical Engineering, Automation and Control Systems (MEACS2015) - Rygina M.; Krisina O.; Ivanov Yu. F. Yuriy Fedorovich; Petrikova E.; Teresov A. (Materials Science in Mechanical Engineering, 2016)
Title screen